Introduksi Konstruk Over-Ekspresi Kandidat Gen OsWRKY76 melalui Agrobacterium tumefaciens pada Tanaman Padi Nipponbare - Aniversari Apriana; Atmitri Sisharmini; Wening Enggarini; Sudarsono Sudarsono; Nurul Khumaida; Kurniawan Rudi Trijatmiko (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2011)
Delivering of Over-Expression Construct OsWRKY76Candidate Gene in Rice cv. Nipponbare throughAgrobacterium tumefaciens. Aniversari Apriana, AtmitriSisharmini, Wening Enggarini, Sudarsono, Nurul.Khumaida, and Kurniawan R. Trijatmiko. Plant geneticimprovement can be done through classical breeding orgenetic engineering. WRKY is a transcription factor involvedin regulating plant defense responses. OsWRKY76 gene islocated in a narrow segment of chromosome 9 which isidentified previously to be related to wide spectrumresistance in rice. A sequence of OsWRKY76 (+1.200 bp)has available in the gene bank and it makes possible toisolate, clone, and construct the gene into over-expressionvector. The aim of this research was to assemble an overexpressionconstruct of OsWRKY76 candidate gene andintroduce it into rice through Agrobacterium-mediatedtransformation. A construct of pCAMBIA-1301::35S::OsWRKY76 has been successfully assembled andtransformed into embryogenic calli of rice cv. Nipponbareusing A. tumefaciens strain Agl-1 and EHA 105. A number of126 independent lines has been produced, in which Agl-1showed 3.8 times more efficient than EHA 105. PCR analysisof randomly selected 25 independent lines showed that allof them positively contained hptII gene, a selectable markerused in the over-expression construct of the OsWRKY76candidate gene. Based on the result, it could be concludedthat the over-expression construct of OsWRKY76 candidategene have been successfully introduced into the tissue ofNipponbare.